Motivating Factors of Aphid Behavior - Kruse, Amy; Hicks, Russell; McCornack, Brian (My University, 2017)
Aphids are small, soft-bodied insects with long slender mouthparts used to pierce leaves and extract fluids; to check for aphid infestation, one must check the underside of the leaf as this is the preferential side for many aphid species [1]. Sugarcane Aphids, Melanaphis sacchari, cause serious damage to sorghum growth, development and productivity in many countries [2]. We hoped to find with this experiment what factors can best explain why Sugarcane Aphids colonize on the underside of sorghum. We found that the only two treatments that were statistically significant (mesh top/cardboard bottom, and mesh top/mesh bottom flipped) meaning that with further research we may be able to prove light is the most motivating factor of aphid colonization behavior.
Citation: Kruse, A. (2017). Motivating Factors of Aphid Behavior . 1st Annual Undergraduate Research Experience in Entomology Symposium, November 16, 2016. Manhattam, KS.